Path Planning for Autonomous Vehicle Ensuring Reliable Driverless Navigation and Control Maneuver - Zakir Abdul Hamid, Umar; Sezer, Volkan; Li, Bin; Huang, Yanjun; Aizzat Zakaria, Muhammad (IntechOpen, 2019)
Path Planning (PP) is one of the prerequisites in ensuring safe navigation and manoeuvrability control for driverless vehicles. Due to the dynamic nature of the real world, PP needs to address changing environments and how autonomous vehicles respond to them. This book explores PP in the context of road vehicles, robots, off-road scenarios, multi-robot motion, and unmanned aerial vehicles (UAVs ).